Автоматизована установка для намагнічування висококоерцитивних магнітів електромагнітних приводів - Сіренко, Микола Миколайович; Горкунов, Борис Митрофанович; Львов, Сергій Геннадійович; Лисенко, Володимир Валерійович (ВКФ "Фавор ЛТД", 2020)
Статтю присвячено актуальній темі розроблення автоматизованої установки з оптимальними енергетичними і масо-габаритними параметрами для якісного намагнічування магнітів електромагнітних приводів зі збереженням цілісності їх обмоток. Розроблено методику розрахунку амплітуди і тривалості імпульсу намагнічування. Визначено час наростання його переднього фронту, який задовольняє умовам повного промагнічування магнітопроводу привода та збереження при цьому цілісності його обмотки збудження. Для формування імпульсу із заданими параметрами запропоновано електронний пристрій на основі зворотного зв’язку між обмоткою привода й імпульсним джерелом струму обмотки індуктора. Запропоновано методику синтезу магнітної системи індуктора за критеріями: досягнення заданої напруженості магнітного поля в робочому об’ємі індуктора; мінімальні габарити джерела живлення і його споживана енергія за намагнічування. Її результатом є отримання профілю перерізу каркаса індуктора з конкретними розмірами і числом витків обмотки. На основі комплексу отриманих результатів у роботі розроблено схему автоматизованої установки і запропоновано компоновку пульту управління і контролю необхідними пристроями та елементами.

The paper is about the development of an automated unit with optimum energy and mass-dimensional parameters for high-quality magnetization of magnets of electromagnetic drives, while preserving the integrity of their windings. The authors develop an approach for calculating amplitude and width of magnetization pulse. The authors than estimate the rise time of leading edge of the pulse, with respect to conditions of complete magnetization of the electromagnetic drive’s magnetic conductor and preservation of its excitation winding integrity. For the formation of the magnetization pulse with given parameters, the authors propose an electronic device, which feedbacks bitween the drive winding and the pulse current source, which provides power to the inductor winding. The authors propose a method of the inductor magnetic system synthesis by criteria of: given magnetic field strength in inductor’s operating volume; power supply unit minimal dimensions and it power consumption while magnetizing. The final result is obtaining cross-section profile of the inductor electrical coil with certain dimensions and number of winding’s turns of a wire of certain diameter. In order to optimize the mass, size, magnetic and energy parameters of the inductor, the authors solve a problem of synthesizing its magnetic system in way of calculating the parameters of the magnetic field for operating volume of the inductor. It is determined by the characteristic overall dimensions of the NZTB type electromagnetic drives (brakes, 0.2 m in diameter), which were subject to magnetization in a field with strength of at least 400 A/m. The result is the determination of geometrical parameters and the crosssection profile of the inductor electrical coil. This profile ensures the uniformity of the magnetic field when magnetizing the electromagnetic drive of given overall dimensions. On the basis of all these results, the authors develop the functional scheme of the automated unit and propose a structure of a panel for monitoring and management of devices and units involved.
Automated Unit for Magnetization of Strong Magnets of Electromagnetic Drives
Keywords: електромагнітні приводи; намагнічування; індуктор; магнітопровід; магнітна система; імпульс намагнічування; автоматизована установка; electromagnetic drives; magnetization; inductor; magnetic conductor; magnetic system; magnetization impulse; automated unit